HUBUNGAN HASIL PEMERIKSAAN SGOT DENGAN SGPT PADA PASIEN DEMAM BERDARAH DI LABORATORIUM PATOLOGI KLINIK RSUD WANGAYA KOTA DENPASAR - I Made Sumertayasa; Anak Agung Ayu Eka Cahyani; Putu Ayu Parwati (PT. GIAT KONSELING NUSANTARA, 2026)
Dengue Fever is an acute febrile illness caused by the dengue virus and transmitted by the Aedes aegypti mosquito. The target organ of the dengue virus is the liver, and mild transaminitis is common in patients with dengue virus infection. Serum Glutamic Oxaloacetic Transaminase (SGOT) Serum glutamic pyruvate transaminase (SGPT) levels usually return to normal levels within 1-2 weeks. The pathogenesis of acute liver failure in patients with dengue is thought to be caused by the direct effect of the dengue virus on liver cells or due to an abnormal immune response to the dengue virus. This study was conducted with secondary data collected from January to June 2025. This type of study is a correlational study with a sample size of 54 people. The results of the SGOT examination in dengue fever patients with a minimum value of 37 U/L, a maximum of 96 U/L, a mean of 71.24 U/L and an SD of 13.67 U/L. The results of the SGPT examination of dengue fever patients obtained a minimum value of 35 U/L, a maximum of 69 U/L, a mean of 53.54 U/L and SD of 7.14 U/L. The results of the Pearson Product Moment correlation test obtained a p-value of 0.000 (p-value <0.05). This indicates a relationship between the results of the SGOT examination and SGPT in DHF patients. The increase in SGOT and SGPT in dengue patients is a result of liver cell injury considering that the dengue virus attacks the reticuloendothelial system of the host. This liver injury is due to the direct effect of the virus, but can also be caused by the host's immune response. One of these is the involvement of CD4+ cytotoxic T cells. This interaction causes the destruction of cells that present viral antigens and cells that do not present antigens in surrounding cells that also express Fas.